A pragmatic low carbohydrate diet intervention changes neither carbohydrate consumption nor glycemia in adolescents and young adults with type 1 diabetes in a randomized trial. Issue 7 (5th September 2022) - Duffus, Sara H.; Slaughter, James C.; Cooley, William; Sharif, Navila; Rainer, Kimberly; Coate, Katie C.; Jaser, Sarah S.; Moore, Daniel J.; Niswender, Kevin D.; Gregory, Justin M.
Abstract: Objective: Despite enthusiasm for low carbohydrate diets (LCDs) among patients with type 1 diabetes (T1DM), no prospective study has investigated outcomes in adolescent T1DM. We aimed to quantify a pragmatic LCD intervention's impact on glycemia, lipidemia, and quality of life (QOL) in adolescents with T1DM. Research Design and Methods: At an academic center, we randomized 39 patients with T1DM aged 13–21 years to one of three 12‐week interventions: an LCD, an isocaloric standard carbohydrate diet (SCD), or general diabetes education without a prescriptive diet. Glycemic outcomes included glycosylated hemoglobin (HbA1c) and continuous glucose monitoring. Results: There were no significant differences in glycemic, lipidemic, or QOL parameters between groups at any timepoint. Median HbA1c was similar at baseline between groups and did not change appreciably (7.9%–8.4% in LCDs, 7.9%–7.9% in SCDs, and 8.2%–7.8% in controls). Change in carbohydrate consumption was minimal with only one participant reaching target carbohydrate intake. Conclusions: This pragmatic LCD intervention did not alter carbohydrate consumption or glycemia. Although this study was unable to evaluate a highly controlled LCD, it indicates that adolescents are unlikely to implement an educational LCD intervention in routine clinic settings. Thus, this approach is unlikely to effectively mitigate hyperglycemia in adolescents.